SİBER GELİŞMELERİN SAĞLIK HİZMETLERİNE YANSIMASI VE GÜVENLİK - GÜLER, Büşra (Cyberpolitik Journal, 2019)
The health industry is evolving from being hospital- and doctor-centered to a patient-centered position. Connecting medical devices to hospital information technology networks provides important benefits for patients. When the patients change the hospital and doctors on the same subject, there is no need to renew the medical workup and medical analyzes. On the other hand, patient losses will be minimized by not reaching the hospital or by misdiagnosis and treatment. Electronic medical record systems provide more accurate care. Insulin pumps, heart rate regulating defibrillators, pacemakers, drug injection pumps, magnetic resonance imaging (MR) devices, heart monitors are widely used in hospital computer networks. The data provided by these devices provide great benefits for the doctor and the patient. It is known that if the necessary cyber security measures are not taken / cannot be taken, it will cause great damages. Easy access points integrated in healthcare, legacy systems, insufficient updates will make it more vulnerable to attacks. Hospital and patient information is more exposed to ransom cyber attacks. Personal health information returns ten times more than credit card information. Therefore, health services are vulnerable to cyber attacks because of their economic or political benefits. There will be more attacks in the future and some of them will be successful. Important goals of cyber security are patient safety and protecting private information. Further investment in health technologies should be made to achieve the expected efficiency and to secure patient information. The continuation of the healthy and normal lives of the patients depends on the fact that manufacturers and practitioners develop safer software.